POLITICAL EVOLUTION OF THE CAMBODIAN GOVERNMENT (1993-PRESENT) - TEP, Sok; HAP, Phalthy (Srawung: Journal of Social Sciences and Humanities, 2022)
This research is mainly based on the Constitution, the law on the organization and functioning of the Cabinet and other laws and online resources. The article reflects the process of state administration activities of the Government of Cambodia. The Paris Agreement of October 23, 1991 required Cambodia to adhere to a liberal, multi-party democracy. The government had two prime ministers and co-ministers in key ministries. In 1998, there was another coalition government. In 2003, there was another coalition government. In the 2007 election, the CPP won a landslide victory of 90 seats to form a single government. In the 2013, the CPP won only 68 seats, according to the 50% plus one formula, leading to the formation of a single government. The 2018 election is an election in the absence of the CNRP. Therefore, the CPP won in all National Assembly 125/125. The new government was formed in the form of a reform of the Royal Government, with only 45 members accountable to the Prime Minister and Parliament. The evolution of the Cambodian government from multi-party to one-party (2018) led to national and international concerns about the collapse of multi-party liberal democracy in Cambodia. The article also found that there have been six mandates of multi-lateral government except the latest one, which political deadlocks always occurs after the national elections, and how they are solved. Therefore, all political parties, including the opposition, should be allowed to participate in free, fair and transparent elections.